Utilidad de expedientes odontológicos disponibles en Costa Rica en el año 2018 para la identificación de víctimas de desastres según el protocolo de INTERPOL - Fernández Chaves, José Manuel (2020)
Introduction: The identification by dental methods has proven its effectiveness for a long time, but in recent years it has played a determining role in the identification of victims of mass disasters and crimes against humanity. One of the determining factors for positive identification is the quality of antemortem information. The purpose of the present investigation was to establish the quality of the information collected in the dental records during the year 2018 in Costa Rica with respect to the information contemplated in the INTERPOL protocols. Materials and methods: Descriptive cross-sectional study, in which a questionnaire was conducted based on the information requested in the INTERPOL antemortem and postmortem forms for identification of disaster victims (DVI). A pilot questionnaire was carried out and applied to 10 dentists, later a calibrated final questionnaire was done electronically through the College of Dental Surgeons of Costa Rica in the Google Docs platform; the results were analyzed by means of frequency distributions, crossing of variables, comparison of means based on analysis of variance. The minimum confidence level for the comparisons was 95%. The statistical processing of the data was done in the database called SPSS version 17.0 and in Excel. Results: A total of 573 questionnaires were answered, of which 76% are women; the distribution is independent of age (p = 0.161). 90.2% of dentists generally elaborate a dental clinical record for their patients, 8.4% sometimes do not and 1.4% do not always do it. 69% of the interviewees indicate that the information that they collect in the dental clinical file can be useful for the identification of a person, 19% indicate that they do not know that this information can be used for identification and 12% indicate that it is not Useful. Conclusions: The dental clinical file is extremely useful to collaborate in the process of identification of fatalities, however there is a large amount of non-dental information that can be collected by dentists to facilitate the identification of human beings.